1977
DOI: 10.1126/science.141098
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Diabetes Reduces Circulating 1,25-Dihydroxyvitamin D in the Rat

Abstract: Duodenal calcium absorption and a vitamin D-dependent duodenal calcium-binding protein are depressed in rats with alloxan- or streptozotocin-induced diabetes. To test for possible abnormal vitamin D metabolism in diabetes we measured serum concentrations of 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D in control, streptozotocin diabetic, and insulin-treated diabetic rats. The serum concentration of 1,25-dihydroxyvitamin D was depressed in untreated diabetic rats to one-eighth of the level in controls and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(65 citation statements)
references
References 33 publications
6
57
1
1
Order By: Relevance
“…Intestinal calcium absorption has been shown to be impaired in the diabetic state (20)(21)(22). The increase in serum calcium concentration in STZ-diabetic rats may result from the release of calcium from bone tissues; the femoral calcium content was found to decrease markedly in STZdiabetic rats.…”
Section: Discussionmentioning
confidence: 95%
“…Intestinal calcium absorption has been shown to be impaired in the diabetic state (20)(21)(22). The increase in serum calcium concentration in STZ-diabetic rats may result from the release of calcium from bone tissues; the femoral calcium content was found to decrease markedly in STZdiabetic rats.…”
Section: Discussionmentioning
confidence: 95%
“…We have no explanation for these discordant findings. In most studies that have used male diabetic rats, total 1,25(OH) 2 D 3 concentrations were found to be lower than in the control group in SZ-induced diabetes (Schneider et al 1977, Hough et al 1982, Wilson et al 1982, Nyomba et al 1985, Romero et al 1995 as well as in spontaneous diabetes (Nyomba et al 1989, Verhaeghe et al 1990. However, we have repeatedly found that 1,25(OH) 2 D 3 concentrations in female nongravid diabetic BB rats remain within the control range, both in rats fed a standard diet and in rats fed a restricted Ca-P diet (Verhaeghe et al , 1989(Verhaeghe et al , 1994; in contrast, pregnant and lactating diabetic rats do have lower 1,25(OH) 2 D 3 concentrations (Verhaeghe et al 1986(Verhaeghe et al , 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Serum PTH concentrations were reported to be increased (Schedl et al 1978) or normal (Romero et al 1995) after 9 days of SZ-induced diabetes, but suppressed after 25 (Romero et al 1995) or 48 days (Hough et al 1982) of SZ-induced diabetes. Decreased 1,25(OH) 2 D 3 levels have been reported repeatedly in male SZ-induced diabetic rats (Schneider et al 1977, Hough et al 1982, Wilson et al 1982, Nyomba et al 1985, Romero et al 1995 and in male spontaneously diabetic rats (Nyomba et al 1989, Verhaeghe et al 1990; interestingly, this is not the case in female nongravid spontaneously diabetic rats (Verhaeghe et al , 1989(Verhaeghe et al , 1994. Renal cortical slices from male diabetic rats produced less 1,25(OH) 2 D 3 but more 24,25(OH) 2 D 3 than control rats (Wongsurawat et al 1983); however, kidneys are larger relative to body weight in diabetic rats (Pillion et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal calcium absorption has been shown to be impaired in the diabetic state. 30,31) The increase in serum calcium concentration in STZ-diabetic rats may result from the release of calcium from bone tissues; the femoral calcium content was found to decrease markedly in STZ-diabetic rats. The oral administration of the extract to these rats had a significant preventive effect on hypercalcemia and bone calcium loss in the diabetic state; intake of the extract may thus have an inhibitory effect on bone resorption in these rats.…”
Section: Discussionmentioning
confidence: 99%